ANALISIS KESIAPAN SEKOLAH MENGHADAPI PELAKSANAAN UNBK DI SMAN 1 SUNGAI AMBAWANG - Muna, Anita Faizul; Witarsa, Witarsa; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the level of readiness of a school in implement Computer-based National Examination. This research is locating in SMA Negeri 1 Sungai Ambawang. This research is qualitative research with descriptive approach. Data collection techniques are carried out by doing the interview, observation and documentation. The validity of the data was triangulated by techniques and sources. Analysis data techniques includes data collecting, reduction, data presentation, conclusions. The results of the research show 1) The readiness regarding facilities and infrastucture is good, seen from the facilities and the equipments such as network specification, computer server specification and participants computer specification, adequate room specifications then server and network has been tested 3 times as the beginning step to preparation. 2) the students’ confidence and optimistic to Computer-based National Examination because in SMA Negeri 1 Sungai Ambawang has done various ways in learning involve computer media and the simulation also must carry out. 3) to improve the learners’s motivation, The teachers give learning by computer media implementation. Keywords: Readiness of the school, Computer-based National Examination.